Alexander the Great: Head to Head with CTE (Chronic Traumatic Encephalopathy) - Alexandra F. Morris (Athens Journal of History, 2017)
One of history’s lingering questions involves the dramatic personality and behavior changes of Alexander the Great. How did a man who was regarded as intelligent, charismatic, compassionate, judicious and composed become increasingly irrational, paranoid, maudlin, mercurial and irascible? Surprisingly, the answer is in today’s headlines concerning concussions and traumatic brain injuries. Alexander the Great most likely suffered from Chronic Traumatic Encephalopathy (CTE), a degenerative brain disease caused by the repeated concussions he sustained both on and off the battlefield. This paper will examine the injuries Alexander sustained, in addition to his health and personality changes through the lens of Chronic Traumatic Encephalopathy. Furthermore, this paper will show that Alexander the Great was neither a megalomaniac nor an alcoholic. Instead Alexander was probably suffering from the effects of CTE as chronicled by the ancient historians, Arrian, Quintus Curtius Rufus, Diodorus, Justinus, and Plutarch.